Analysis of the CRK expressions in bottle gourd (Lagenaria siceraria) under Fusarium oxysporum f. sp. lagenariae stress by using genome-wide identification strategy - Preetinanda Sahoo; Ikram Ullah; Debarpita Sahoo; Chirasmita Bose; Muhammad Amir Zia; Sumaira Salahuddin Lodhi; Mahmoud F. Seleiman; Nawab Ali; Gagan Kumar; Suhail Asad; Satyabrata Nanda (BMC Genomics)
Abstract Background The cysteine-rich receptor-like kinases (CRKs) family in plants have been reported to perform multiple functions against various stresses. However, the CRK family in bottle gourd (Lagenaria siceraria) has not been well-explored. Herein, a comprehensive genome-wide identification and characterization of the CRK gene family has been carried out in bottle gourd under Genome-wide characterization of CRK genes in bottle gourds under Fusarium oxysporum f. sp. lagenariae infection. Results A stringent set of bioinformatic analyses identified 18 LsCRKs in the bottle gourd genome. Chromosomal mapping of the identified LsCRKs revealed that the LsCRKs were distributed in 4 chromosomes in the bottle gourd genome. The phylogenetic analysis of LsCRKs divided them into two subgroups on the tree. The synteny and collinearity analysis of the LsCRKs among themselves and other plant CRKs provided insights into their conservancy and expansion. Gene ontology analysis of the identified LsCRKs suggested their possible roles in regulating different physiological processes and stress responses in bottle gourd. To assess the involvement of the LsCRKs under F. oxysporum f. sp. lagenariae infection, bottle gourd seedlings were transplanted into the pots with F. oxysporum-infected soil. The expression analysis revealed that multiple LsCRKs exhibited induced expression, suggesting their involvement in bottle gourd-F. oxysporum interactions. Additionally, the protein-protein interaction analysis suggested some important interacting partners of LsCRKs crucial to different physiological processes in bottle gourd. Conclusions The present work explored and analyzed the LsCRKs in bottle gourd. Functional predictions and interaction network analysis suggested the roles of LsCRKs in modulating multiple physiological processes in bottle gourd. The expression dynamics of LsCKRs under fungal pathogen infection suggest their involvement in stress response in bottle gourds. Overall, the results of the study provide basic information about the CRK family in bottle gourds and their involvement in fungal pathogen response.